Integrated Law Enforcement in Handling of Local Election (Pemilukada) Criminal Actions in 2018/2019 - Iwan Iwan; Sri Kusriyah (Universitas Islam Sultan Agung, 2021)
The objectives of this research are: To find out and analyze integrated law enforcement in post-conflict local election 2018/2019 criminal cases. To find out and analyze the obstacles in the integrated law enforcement of the 2018/2019 post-conflict local election criminal acts and their solutions. The method used by researchers is juridical sociological approach to law and the specification in this research is including analytical descriptive. As for the sources and types of data in this study are primary data and secondary data obtained from literature studies. Based on the results of that research of Integrated Law Enforcement in Criminal Cases in the 2018/2019 Pemilukada is by the Police, Attorney General's Office and Panwaslu who are members of the Integrated Law Enforcement Center (Gakkumdu), by adjusting the criminal justice system as generally regulated in the KUHAP, including investigations by the Police, prosecution by Prosecutors and criminal decisions by the Court. The obstacle is due to the lack of criminal threats so that there are still many people who feel they are not deterred and want to take advantage of the existing situation without thinking about anything else, while in the law enforcement factor there is a lack of members or investigators who are truly competent in handling the case so that the investigation process a little constrained.